2014
DOI: 10.4067/s0718-48082014000200009
|View full text |Cite
|
Sign up to set email alerts
|

Cooperación en las Ciencias del Comportamiento Latinoamericanas: Una Investigación Documental

Abstract: ResumenUna investigación basada en el Psycinfo, desde 2001 hasta 2010, sobre la cooperación científica entre al menos dos países latinoamericanos, en Ciencias del Comportamiento, resultó en 528 publicaciones. Los países con mayor participación fueron Brasil, México, Argentina, Colombia, Chile y Perú. Las publicaciones incluyen 281producciones exclusivamente latinoamericanas y 247 publicaciones con la participación de uno o más países de otros continentes. Las tres áreas con el mayor número de publicaciones han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 10 publications
1
9
0
7
Order By: Relevance
“…According to Katz and Martin (1997), co-authorship is the basic unity to evaluate cooperation. This intensification is also observed in Latin American science (García, Acevedo-Triana & López-López, 2014). Fernán-dez, Gómez and Sebastián (1998) observed that 31.7 % of all scientific publications between 1991 and 1995 were coauthored; however, partnerships with other Latin American countries were less frequent than partnerships with European countries and the USA.…”
Section: Introductionmentioning
confidence: 93%
“…According to Katz and Martin (1997), co-authorship is the basic unity to evaluate cooperation. This intensification is also observed in Latin American science (García, Acevedo-Triana & López-López, 2014). Fernán-dez, Gómez and Sebastián (1998) observed that 31.7 % of all scientific publications between 1991 and 1995 were coauthored; however, partnerships with other Latin American countries were less frequent than partnerships with European countries and the USA.…”
Section: Introductionmentioning
confidence: 93%
“…Using the Scopus database, we examined psychology production with a focus on authors and institutional affiliation between at least two different countries to define the collaboration (Garcia et al, 2014). We developed two bibliometric maps according to the methodology described by Hassan-Montero et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…One way to measure international collaboration is through the analysis of output from researchers, joint projects, academic events, and research training (Chinchilla-Rodríguez et al, 2009;Garcia et al, 2014). Following Chinchilla-Rodríguez et al (2009), we understand that collaboration is the reflection of an individual and institutional process that promotes generation of output, first and foremost which are scientific articles.…”
mentioning
confidence: 99%
See 2 more Smart Citations